The Impact of Foreshortening on Regional Strain – A Comparison of Regional Strain Evaluation Between Speckle Tracking and Tissue Velocity Imaging - Tarr, A.; Stöbe, S.; Trache, T.; Kluge, J.-G.; Varga, A.; Pfeiffer, D.; Hagendorff, A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: The conventional parameter of systolic function is global left ventricular (LV) ejection fraction (EF), but this parameter will be replaced by global strain because it seems to be more robust. However, regional strain differences can have a significant impact on global strain. Thus, the aim of the present study was to evaluate the effect of non-standardized scanning on regional strain values determined by 2D speckle tracking and tissue velocity imaging (TVI). Regional longitudinal peak systolic strain (PSS) was measured in standardized data sets of the apical 4-chamber view (ChV) and in a standardized oblique foreshortened view in patients with normal wall motion patterns. Materials and Methods: A standardized 4ChV and a foreshortened 4ChV – defined by distinct cardiac structures – were acquired using a Vivid E9 system in 54 patients. All regional PSS values measured in monoplane 2D loops in lateral and septal regions were analyzed to detect the differences between regional strain measured in the standard and the foreshortened view. Results: Significant PSS differences due to FS were detected in patients using 2D speckle tracking for the basal septal regions (p < 0.001). No significant differences due to FS were detected in patients during the analysis of TVI-based strain values (p > 0.05, paired sample T-test). Conclusion: To our knowledge this is the first study focusing on methodological aspects – especially standardization – using speckle tracking and TVI. Due to the lower accuracy of strain calculation based on TVI in basal regions, foreshortening has no significant impact on quantitative parameters of TVI-derived strain values in normal contracting hearts. Using speckle tracking, however, foreshortening induces significant differences of basal septal strain in normal contracting hearts. In the presence of regional wall motion defects, a lack of standardization of the views will cause inhomogeneous patterns of regional strain depending on the scan planes through the center of the infarction or its penumbra. Thus, non-standardization will have a significant impact on deformation parameters in 2D echocardiography.
Keywords: heart; ultrasound 2 D; technical aspects; foreshortening; peak systolic strain